Altered TDP‐43‐dependent splicing in HSPB8‐related distal hereditary motor neuropathy and myofibrillar myopathy. (2nd December 2017) - Cortese, A.; Laurà, M.; Casali, C.; Nishino, I.; Hayashi, Y. K.; Magri, S.; Taroni, F.; Stuani, C.; Saveri, P.; Moggio, M.; Ripolone, M.; Prelle, A.; et al.
Abstract : Background and purpose: Mutations in the small heat‐shock protein 22 gene ( HSPB8 ) have been associated with Charcot‐Marie‐Tooth disease type 2L, distal hereditary motor neuropathy (dHMN) type IIa and, more recently, distal myopathy/myofibrillar myopathy (MFM) with protein aggregates and TDP‐43 inclusions. The aim was to report a novel family with HSPB8 K141E ‐related dHMN/MFM and to investigate, in a patient muscle biopsy, whether the presence of protein aggregates was paralleled by altered TDP‐43 function. Methods: We reviewed clinical and genetic data. We assessed TDP‐43 expression by qPCR and alternative splicing of four previously validated direct TDP‐43 target exons in four genes by reverse transcriptase–polymerase chain reaction. Results: The triplets and their mother presented in the second to third decade of life with progressive weakness affecting distal and proximal lower limb and truncal muscles. Nerve conduction study showed a motor axonal neuropathy. The clinical features, moderately raised creatin kinase levels, selective pattern of muscle involvement on magnetic resonance imaging and pathological changes on muscle biopsy, including the presence of protein aggregates, supported the diagnosis of a contemporary primary muscle involvement. In affected muscle tissue we observed a consistent alteration of TDP‐43‐dependent splicing in three out of four TDP‐43‐target transcripts ( POLDIP3, FNIP1 and BRD8 ), as well as a significant decrease of TDP‐43 mRNA levels. Conclusions: Our study confirmed the role of mutated HSPB8 as a cause of a combined neuromuscular disorder encompassing dHMN and MFM with protein aggregates. We identified impaired RNA metabolism, secondary to TDP‐43 loss of function, as a possible pathological mechanism of HSPB8 K141E toxicity, leading to muscle and nerve degeneration.